2012
DOI: 10.1038/bjc.2012.92
|View full text |Cite
|
Sign up to set email alerts
|

A novel, externally validated inflammation-based prognostic algorithm in hepatocellular carcinoma: the prognostic nutritional index (PNI)

Abstract: Background:There is increasing evidence that the presence of an ongoing systemic inflammatory response is a stage-independent predictor of poor outcome in patients with cancer. The aim of this study was to investigate whether an inflammation-based prognostic score, the prognostic nutritional index (PNI), is associated with overall survival (OS) in patients with hepatocellular carcinoma (HCC).Methods:All patients with a new diagnosis of HCC presenting to the Medical Oncology Department, Hammersmith Hospital bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
340
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(364 citation statements)
references
References 57 publications
16
340
3
5
Order By: Relevance
“…Previous stud- ies have shown that elevated NLR and PLR at the baseline were associated with worse OS and disease-free interval in resected and advanced cancers (Proctor et al 2011;Lee et al 2013;Paramanathan et al 2014;Pinato et al 2014). PNI is not commonly used as a score for the measurement of systemic inflammatory responses, and a study of hepatocellular carcinoma (HCC) found that PNI was an independent and externally validated predictor of poor OS in patients with HCC (Pinato et al 2012). Only two studies have focused on the value of NLR for prognosis in SCLC, with the results indicating that elevated NLR could predict worse OS and PFS (Kang et al 2014;Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous stud- ies have shown that elevated NLR and PLR at the baseline were associated with worse OS and disease-free interval in resected and advanced cancers (Proctor et al 2011;Lee et al 2013;Paramanathan et al 2014;Pinato et al 2014). PNI is not commonly used as a score for the measurement of systemic inflammatory responses, and a study of hepatocellular carcinoma (HCC) found that PNI was an independent and externally validated predictor of poor OS in patients with HCC (Pinato et al 2012). Only two studies have focused on the value of NLR for prognosis in SCLC, with the results indicating that elevated NLR could predict worse OS and PFS (Kang et al 2014;Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying prognostic factors before surgery to help determine the optimal preoperative therapy and timing of surgery is important. Previous attempts have focused on a number of immuno-nutritional indices, including PNI, NLR, PLR, PI, and GPS [4,6,7,9,15,21,[25][26][27] . However, their reported prognostic value can vary between studies of the same cancer type; for example, in hepatocellular carcinoma, PLR was found to be a prognostic marker in one study, but another study suggested that only PNI was a prognostic marker [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Its application as a prognostic marker was recently suggested by some researchers, and it was recently used to predict prognosis in a number of malignancies, including pancreatic, hepatocellular, and colorectal carcinoma. However, its prognostic significance in gastric cancer has not been fully studied, and the mechanisms that link PNI to outcome remain unclear [7][8][9] . In addition to PNI, markers of systematic inflammation, such as the number of white blood cells, neutrophils, platelets, and lymphocytes, and the indices derived from these, including the neutrophil-lymphocyte ratio (NLR) [10,11] and platelet-lymphocyte ratio (PLR), have also been used as prognostic markers.…”
Section: Introductionmentioning
confidence: 99%
“…51 Prognostic nutritional index, has been found to be independently associated with overall survival in patients with hepatocellular carcinoma. 52 It is known that patients with weight loss and muscle wasting have poorer clinical outcomes than patients without such weight loss or muscle wasting. As a consequence, efforts have been made to supply nutrients with the intent of improving the nutritional status.…”
Section: Nutrition Management In Terminal Stage Hepatocellular Carcinomamentioning
confidence: 99%